Antibacterial, biological, and physico-mechanical properties of a 1,3,5- triacryloylhexahydro-1,3,5-triazine containing luting agent - Oliveira, Naiara Araújo de (2020)
Objectives: The aim of this study was to formulate and evaluate an experimental luting agent with the addition of 1,3,5-triacryloylhexahydro-1,3,5-triazine (TAT). Materials and Methods: Experimental luting agents were obtained by mixing 50wt% Bisphenol A-Glycidyl Methacrylate (BisGMA), 30wt% Urethane Dimethacrylate (UDMA), 20wt% Triethylene Glycol Dimethacrylate (TEGDMA) and initiators. Barium silicate glass was used as a filler (45wt%). The TAT was added to the filling agents at 15wt% concentration as an antibacterial monomer (CTAT). One group remained without triazine as the control (CCONTROL). The experimental luting agents were evaluated by their degree of conversion, film thickness, flow, flexural strength, softening solvent, cytotoxicity and antibacterial activity. The microshear bond strength test (SBS) was evaluated in different substrates after 7 and 30 days. Data were analysed by the Students t-test one-way ANOVA and for SBS, three-way ANOVA with Tukey post hoc test (=0.05). Results: CTAT showed a higher degree of conversion (immediately and after 7 days). The film thickness was in accordance with ISO 4049 in both groups. Lower cytotoxicity and lower softening solvent were observed for CTAT when compared to the control. No statistical difference was shown between the groups for flow, flexural strength, in planktonic analysis and in antibacterial activity analysis. Reduced biofilm formation was observed in the CTAT group. CTAT resulted in higher SBS values after 7 days of storage when applied on Y-TZP ceramics. Conclusion: The experimental luting agent with TAT showed antibiofilm activity, increased degree of conversion and decreased the cytotoxicity. In addition, increased the bond strength in a Y-TZP substrate.